Prevalence and Characterization of Cryptosporidium Species and Genotypes in Four Farmed Deer Species in the Northeast of China - Zhao, Wei; Xu, Jie; Xiao, Mengran; Cao, Jianping; Jiang, Yanyan; Huang, Huicong; Zheng, Bin; Shen, Yujuan (Frontiers in Veterinary Science, 2020)
Cryptosporidiosis is a primary cause of diarrhea in both humans and farm animals. It can be transmitted from farmed animals to humans by direct contact or through contaminated equipment. In this study, we analyzed the occurrence and the genetic characterization of Cryptosporidium in farmed deer in northeastern China. 338 fresh fecal specimens were collected from four farmed deer species, including 125 reindeer, 109 red deer, 86 sika deer, and 18 Siberian roe deer. Cryptosporidium was identified by PCR amplification of the partial small subunit of ribosomal RNA (SSU rRNA) gene. Meanwhile, C. ubiquitum isolates were subtyped using PCR and sequence analysis of the 60-kDa glycoprotein (gp60) gene. The overall prevalence of Cryptosporidium was 7.1%, with 15.1% for sika deer, 4.0% for reindeer, 4.6% for red deer, and 5.6% for roe deer. Two Cryptosporidium species and one genotype were identified, including C. ubiquitum (n = 4), C. xiaoi (n = 2) and Cryptosporidium deer genotype (n = 18). All four C. ubiquitum isolates belonged to the XIIa subtype (n = 4). This study confirmed that Cryptosporidium deer genotype was the most common genotype in cervids, and provides the first evidence of the occurrence of C. xiaoi in those animals. Meanwhile, we given the first data on C. ubiquitum and Cryptosporidium deer genotype in reindeer worldwide.